Dialectical Behavior Therapy for Improving Individual Emotional Regulation Ability with Self-Harm - Widyawati, Risma Amelia; Surjaningrum, Endang R. (Psikoborneo: Jurnal Ilmiah Psikologi, 2024)
This study aims to evaluate the effectiveness of Dialectical Behavior Therapy (DBT) in improving emotional regulation skills and reducing self-harm behaviors among university students aged 18–25 with a history of family relationship issues and tendencies toward self-harm. Using a one-group before-and-after experimental design, five participants underwent six DBT intervention sessions, encompassing phases of introduction, problem identification, and emotional regulation strategies. Research instruments included the Self-Harm Inventory (SHI), Emotion Regulation Questionnaire (ERQ), as well as graphic tests, observation, and interviews. Results showed a significant improvement in the cognitive reappraisal aspect and a reduction in expressive suppression in the ERQ, indicating adaptive emotional regulation skill enhancement. Additionally, self-harm scores on the SHI decreased for most participants. Qualitative data also supported these findings, with participants beginning to apply positive strategies such as exercising and socializing with close friends. In conclusion, DBT is effective in helping individuals with self-harm tendencies improve emotional regulation and reduce maladaptive behaviors. Penelitian ini bertujuan untuk mengevaluasi efektivitas Dialectical Behavior Therapy (DBT) dalam meningkatkan kemampuan regulasi emosi dan mengurangi perilaku self-harm pada mahasiswa berusia 18–25 tahun dengan riwayat masalah dalam hubungan keluarga dan kecenderungan self-harm. Menggunakan metode eksperimen one-group before-after design, lima partisipan mengikuti enam sesi intervensi DBT, yang terdiri dari tahapan perkenalan, identifikasi masalah, dan strategi regulasi emosi. Instrumen penelitian berupa Self-Harm Inventory (SHI), Emotion Regulation Questionnaire (ERQ), serta alat tes grafis, observasi, dan wawancara. Hasil menunjukkan peningkatan signifikan pada aspek cognitive reappraisal dan penurunan expressive suppression dalam ERQ, menandakan peningkatan kemampuan regulasi emosi yang adaptif. Selain itu, skor self-harm pada SHI menurun pada sebagian besar partisipan. Data kualitatif juga mendukung hasil ini, dengan partisipan mulai menerapkan strategi positif, seperti berolahraga dan berkumpul dengan orang terdekat. Kesimpulannya, DBT efektif dalam membantu individu dengan kecenderungan self-harm meningkatkan regulasi emosi dan mengurangi perilaku maladaptif.